Whole‐genome sequencing reveals forgotten lineages and recurrent hybridizations within the kelp genus Alaria (Phaeophyceae). Issue 6 (12th October 2021) - Bringloe, Trevor T.; Zaparenkov, Dani; Starko, Samuel; Grant, William Stewart; Vieira, Christophe; Kawai, Hiroshi; Hanyuda, Takeaki; Filbee‐Dexter, Karen; Klimova, Anna; Klochkova, Tatyana A.; Krause‐Jensen, Dorte; Olesen, Birgit; et al.
Abstract : The genomic era continues to revolutionize our understanding of the evolution of biodiversity. In phycology, emphasis remains on assembling nuclear and organellar genomes, leaving the full potential of genomic datasets to answer long‐standing questions about the evolution of biodiversity largely unexplored. Here, we used whole‐genome sequencing (WGS) datasets to survey species diversity in the kelp genus Alaria, compare phylogenetic signals across organellar and nuclear genomes, and specifically test whether phylogenies behave like trees or networks. Genomes were sequenced from across the global distribution of Alaria (including Alaria crassifolia, A. praelonga, A. crispa, A. marginata, and A. esculenta ), representing over 550 GB of data and over 2.2 billion paired reads. Genomic datasets retrieved 3, 814 and 4, 536 single‐nucleotide polymorphisms (SNPs) for mitochondrial and chloroplast genomes, respectively, and upwards of 148, 542 high‐quality nuclear SNPs. WGS revealed an Arctic lineage of Alaria, which we hypothesize represents the synonymized taxon A. grandifolia . The SNP datasets also revealed inconsistent topologies across genomic compartments, and hybridization (i.e., phylogenetic networks) between Pacific A .  praelonga, A .  crispa, and putative A .  grandifolia, and between some lineages of the A .  marginata complex. Our analysis demonstrates the potential for WGS data to advance our understanding of evolution and biodiversity beyond amplicon sequencing, and that hybridization is potentially an important mechanism contributing to novel lineages within Alaria . We also emphasize the importance of surveying phylogenetic signals across organellar and nuclear genomes, such that models of mixed ancestry become integrated into our evolutionary and taxonomic understanding.